[A sheep after giving birth to a calf] - (:unkn) unknown (The Public Relations Department. Caroni (1975) Limited, Trinidad and Tobago, 2013)
The sheep licking the calf after delivery with the afterbirth visible at the rear of the sheep.
Cataloger's title
Keywords: Livestock; Cattle—Parturition -- Trinidad and Tobago; Caroni (1975) Limited